Salidas pedagógicas con niños y niñas de 2 a 4 años en Bogotá: una mirada desde la educación inicial (2020)
A concern shared by early childhood teachers is about the social dynamics in which boys and girls develop in the city, which are usually restricted to architecturally closed environments. This research article analyzes the pedagogical outings as an alternative to this problem, from the perspective of some teachers and the characterization of private unconventional proposals in Bogotá for boys and girls between 2 and 4 years old. The research was proposed from the pragmatic epistemological posture of an exploratory descriptive type. As a research strategy, rapid ethnography was assumed, through which teachers and an expert participated, as well as the information collected from the documentary exploration of secondary information and the visit to some private institutions that offer unconventional education to boys and girls from 2 to 4 years old in Bogotá. The theoretical framework is structured around three categories: urban pedagogy, educating city and initial education. As main finding is identified the preponderant value that teachers give to educational outings as part of their pedagogical intentions with boys and girls. Second, there are the opportunities and perspectives of pedagogical outings, among which are the possibility of contributing to the development of children, and the understanding of the city as an educational content, means and purpose. There are also reflections related to education for diversity and natural environments as a city challenge for boys and girls.